Nghiên cứu khả năng tạo phức của ortho-este tetra azophenylcalix[4]aren (TEAC) với Th(IV) - Hiếu, Trần Quang; Tán, Lê Văn; Tuấn, Nguyễn Ngọc (Vietnam Journal of Chemistry, 2014)
A simple, sensitive and selective spectroscopy method was developed for the determination of Thorium based on complixation between Ortho-Ester Tetra azophenyl Calix[4]arene (TEAC) and Th(IV). In acid media, TEAC formed a 1:1 complex with Th(IV). Beer’s law was obeyed in the range 2.5´10-6 – 2.5´10-5 mol.l-1 of Th(IV). The limited of detection was 1.0´10- 6 mol l-1. This result could be applied for determining concentration of Thorium in various samples, geological, soil and radioactive waste samples. Keywords: Chromoionophore; Calixarene; Thorium, Spectroscopy.